Farmers' Attitude Towards e-Agriculture in Bangladesh - Md. Rafiquel Islam and Sheikh Mohammed Mamur Rashid (Indian Journal of Extension Education, 2016)
e-Agriculture is being the utmost desire for the sustainable development of worldover. The research was designed toassess farmers' attitude towards e-Agriculture. The methodology of this study is an integration of quantitative andqualitative methods based on data collection in Bhatbour Block of Dhighi union under Sadar Upazila of MinikganjDistrict. Data were collected from 133 e-Agriculture users. Descriptive statistics, multiple regression (B) were used foranalysis. 73.7 percent of the respondents had moderately favorable attitude, 06 percent had low favorable attitude and 20.3percent had high favorable attitude towards e-Agriculture. Variables such as effective farm size, annual householdincome, farming experience, participation in training, knowledge on e-Agriculture, organizational participation andcosmopoliteness had significant contribution on farmers' attitude towards e-Agriculture and these variables contributedtotal 61.9 percent in farmers' attitude towards e-Agriculture. Hence, it is high time prepare the farmers to use these eAgriculture tools for their wellbeing through proper educational activities and to popularize this service, governmentshould implement integrated marketing communication using the popular print and electronic media so that moreand more people get aware of this service.